Efficient synthesis of furfurylamine from biomass via a hybrid strategy in an EaCl:Gly–water medium - He, Wei; He, Yu-Cai; Ye, Jianren (Frontiers in Bioengineering and Biotechnology, 2023)
The objective of this work was to develop an efficient approach for chemoenzymatically transforming biomass to furfurylamine by bridging chemocatalysis and biocatalysis in deep eutectic solvent EaCl:Gly–water. Using hydroxyapatite (HAP) as support, heterogeneous catalyst SO42−/SnO2-HAP was synthesized for transforming lignocellulosic biomass into furfural using organic acid as co-catalyst. Turnover Frequency (TOF) was correlated with the pKa value of the used organic acid. Corncob was transformed by oxalic acid (pKa = 1.25) (0.4 wt%) plus SO42−/SnO2-HAP (2.0 wt%) to produce furfural in the yield of 48.2% and the TOF of 6.33 h-1 in water. In deep eutectic solvent EaCl:Gly–water (1:2, v/v), co-catalysis with SO42−/SnO2-HAP and oxalic acid was utilized to transform corncob, rice straw, reed leaf, and sugarcane bagasse for the production of furfural in the yield of 42.4–59.3% (based on the xylan content) at 180 °C after 10 min. The formed furfural could be efficiently aminated to furfurylamine with E. coli CCZU-XLS160 cells in the presence of NH4Cl (as amine donor). Biological amination of furfural derived from corncob, rice straw, reed leaf, and sugarcane bagasse for 24 h, the yields of furfurylamine reached > 99%, with the productivity of 0.31-0.43 g furfurylamine per g xylan. In EaCl:Gly–water, an efficient chemoenzymatic catalysis strategy was employed to valorize lignocellulosic biomass into valuable furan chemicals.